Factors affecting household savings in selected urban poor barangays in Iloilo City. - Gonzales, Jonathan F. (2014.)
This research is an analysis of the factors that significantly affect household savings in ten urban poor barangays in Iloilo City. Using simple random sampling, 132 households were included in the study. Data was collected through survey and key informant interviews. Results show that household head characteristics such as age, sex, level of education and number of dependents significantly affect household savings. It was also found out that income and household size are important determinants of household savings. Based on the results, this study recommends the provision of livelihood, better access to tertiary education and family planning seminars to increase poor household savings. Likewise, it is also suggested that access of poor households to formal financial institutions be enhanced to encourage savings among them.
Research Paper (Undergraduated, Bachelor of Arts in Economics) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2014.
Keywords: Urban Poor Barangays -- Iloilo City